Intestinal microbiota and cardiovascular diseases: influence of dietary patterns on de the gut heart axis (Research, Society and Development, 2025)
Introduction: The gut microbiota plays an essential role in metabolic and immune health, and its dysregulation has been associated with an increased risk of cardiovascular diseases. Metabolites such as TMAO promote atherosclerotic processes, whereas short-chain fatty acids exert protective effects. In this context, dietary patterns emerge as the main modulator of microbial composition. Objective: The aim of this review was to analyze how the gut microbiota influences the development of cardiovascular diseases and to evaluate the role of dietary patterns in modulating this relationship. Methodology: This study is a systematic review conducted in the PubMed, Lilacs, and Medline databases, including articles published between 2023 and November 2025. After applying the inclusion and exclusion criteria, 11  studies were selected. Results: The results showed that Mediterranean and plant-based diets increase microbial diversity and the abundance of bacteria that produce short-chain fatty acids, which improve cardiometabolic markers. Several studies identified specific species, such as Oscillibacter, associated with lower non-HDL cholesterol levels, suggesting a direct role in lipid metabolism. Microbial metabolites such as PAGln and TMAO were consistently linked to increased inflammation and cardiovascular events. Factors such as sex, ethnicity, and age also influenced the microbial profile associated with cardiovascular risk. In addition, interventions using Lactobacillus plantarum demonstrated a significant reduction in TMAO levels. Conclusion: It is concluded that healthy dietary patterns are essential for optimizing the gut microbiota and reducing cardiovascular risk.